Genetic resources of pulse crops in India: An overview - Rana, J. C.; Gautam, N. K.; Gayacharan, 1; Singh, Mohar; Yadav, Rashmi; Tripathi, Kuldeep; Yadav, S. K.; Panwar, N. S.; Bhardwaj, Rakesh (The Indian Journal of Genetics and Plant Breeding, 2017)
India is rich in genetic diversity of major pulse crops, butthe productivity and the production of pulse crops remainslow compared to the world and hence, there is a need toenhance the utilization for increasing the production. Majorpulse species for which genetic diversity is occurring inIndia include Vigna,Cajanus,Cicer,Pisum,Lens,Phaseolusand few minor pulses such as Macrotyloma, Canavalia,Lathyrus, Vicia, Mucuna, Moghania and Rhynchosia etc.National Bureau of Plant Genetic Resources (NBPGR) isthe nodal institute for the management of plant geneticresources in India. It has assembled ~70,000 accessions ofdifferent pulse crops majoring Cajanus cajan, Cicerarietinum, Phaseolus vulgaris, Pisum sativum, Vignamungo, Vigna radiata, Vigna umbellata, Vigna unguiculata,Vicea sp. and Lens sp. through collection and introductionfrom India and from >70 other countries of the world. Severalpests of quarantine significance have been identified andsalvaged from the exotic germplasm. The ex situ basecollection at NBPGR conserve 64,744 accessions of 20genera and 61 species of pulses. This germplasm has beencharacterized for agro-morphological, quality andbiochemical traits, biotic and abiotic stresses for identifyingtrait-specific reference sets and 28 catalogues describingabout 45,000 accessions of 14 pulse crops. A total of 121accessions of various pulse crops have been registered asunique/potential donors. Core and mini cores have beendeveloped in chickpea, pigeonpea, common bean,mungbean, adzuki bean, cowpea, lentil, moth bean andpea both nationally and internationally. Wild species ofpulse crops have been utilized for transferring desirabletraits into cultivated species. Application of modern toolsand technologies of molecular biology will accelrate theprocess of gene transfer for improvement of pulse crops.